THE POTENTIAL AND CONTRIBUTIONS HANDICRAFT OF PALM IN HOUSEHOLD INCOME - Sasmita Siregar; Khairunnisa Rangkuti; Dedi Siswanto (JASc (Journal of Agribusiness Sciences), 2017)
This study aims to determine: First, the magnitude Contributions side: oil on household income in the study area. Second, potential side: palm handicraft business in the area of research. Third, constraints - constraints in the development of craft business side: the palm area of research. Fourth, the business development strategy craft palm side: in the study area. Sampling method using census method that takes all the existing sample research area. The analytical method used is descriptive analysis and SWOT analysis.The research result is that the contribution of the craft business side: oil on household income in the village Rabuhit is Rp 44.22825 million ie 56% of total household income. Business development strategies craft side: the oil can be seen from the potential and constraints - constraints faced by producers are expanding the marketing network, the expansion of handicraft business side: oil, providing added value / a touch of creativity that makes the motive side: oil more attractive, maintain good relations with the consumer side: oil and using existing knowledge about the area plantation palm frond waste generators to maintain the availability of the raw materials for  the production of handicraft of palm.Keywords : Potential, Contributions, Profits